2019
DOI: 10.1080/10826084.2019.1618332
|View full text |Cite
|
Sign up to set email alerts
|

Density of Medical Marijuana Dispensaries and Current Marijuana Use among Young Adult Marijuana Users in Los Angeles

Abstract: Background: While tobacco and alcohol studies have focused on density of outlets as a determinant of consumption, research has begun examining the effects of medical marijuana (MM) dispensaries on marijuana use.Objectives: Examine the relationship between density of MM dispensaries and frequency of marijuana use among young adult medical marijuana patients (MMP) and non-patient users (NPU).Methods: Young adult marijuana users (n=329) aged 18-26 years old were sampled in Los Angeles in 2014-15 and separated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…city) and state levels is related to higher prior-year cannabis use, although the details of these findings vary between studies [1][2][3][4][5][6]. Other studies have found that medical cannabis laws do not appear to be related to increased adolescent or young adult cannabis use [7][8][9][10][11] or overall cannabis hospitalizations [12], although they are associated with higher rates of treatment among males [13]. One potential explanation for the heterogeneity in these findings is that the impact of cannabis availability is not evenly distributed throughout states and cities, among age groups or on different types of cannabis use (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…city) and state levels is related to higher prior-year cannabis use, although the details of these findings vary between studies [1][2][3][4][5][6]. Other studies have found that medical cannabis laws do not appear to be related to increased adolescent or young adult cannabis use [7][8][9][10][11] or overall cannabis hospitalizations [12], although they are associated with higher rates of treatment among males [13]. One potential explanation for the heterogeneity in these findings is that the impact of cannabis availability is not evenly distributed throughout states and cities, among age groups or on different types of cannabis use (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, only a small number of publications exist on the topics related to MM dispensaries, and nearly all of these existing studies have focused on patients with specific indications [9,10], comparisons of younger and older MM patients [11,12], perceptions and training related to dispensary staff [13,14], or associations between the MM dispensary and different aspects of the local community [15,16]. Our current study adds to this existing literature by reporting on multiple characteristics within a broad spectrum of MM patients, and to the best of our knowledge is potentially the first study to examine the similarities and differences between male and female MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 20–25% of tobacco smokers were also reported to have acute bronchitis, although the symptoms of tobacco smokers were quite similar to those of marijuana smokers regardless of the graded disproportion in the quantity of each constituent smoked per day, which means that 3 marijuana joints had the same effect as 20 tobacco cigarettes. However, no additional consequences of marijuana and tobacco were observed ( Lankenau et al, 2019 ). A similar type of survey conducted in the residential area of Tucson over a randomly arranged group of individuals in the range of 15–40 years of age reported additive effects of both marijuana and tobacco, which was not noted in the survey conducted in Los Angles ( Chase et al, 2016 ).…”
Section: Marijuana and Health Effects: Conflicting But Interesting Outcomesmentioning
confidence: 99%